Eastern markets in historical perspective - Jezierski, Andrzej; Leszczyńska, Cecylia (Studia Historiae Oeconomicae, 2001)
"The Encyclopedia of Economic History of Poland till 1945," published 20 years ago, contains quite an extensive entry "Eastern markets," which begins in the following way: "Eastern markets, a common name given to an outlet for industrial goods manufactured in the Kingdom of Poland, situated east of the Polish territory, comprising Russia and, at a certain point in history, also China and Manchuria." As follows from the introduction such a concept of eastern markets was very appropriate for the late 19' and early 20 centuries, when the Russian Empire was the eastern neighbour of Poland. From the historical perspective, and - in particular - from the perspective of the year 2000 when Ukraine, Lithuania, and Belorussia became independent countries, the concept of the eastern market assumes a new meaning and it is worth taking a closer look at the range and nature of Polish export in modern times and in the 20th century. A tentative question that we would like to raise here is the following: "If and when in the Polish export to the east did the market outlet include the Ukraine, Belorussia, and Lithuania, and when did it include central Russia and the mythical China?"